Two Schools in the Area of Folk Medicine Practice in Turkey: Healers and Physicians / Türkiye’de Halk Hekimliği Uygulama Alanında İki Ekol: Şifacılar ve Hekimler - Hicran Karataş (Folklor/Edebiyat, 2021)
In the context of folklore discipline, folk medicine is the knowledge related to illness and to recover that has been enhanced throughout the ages and verbally transferred to generations in the area of health. Local and authentic healing methods of folk medicine are coined under the name of traditional medicine (TM) in the eyes of positive sciences. Modern medical scholars preferably use this very nomenclature to address particular folk knowledge formed in healing area that are handed down throughout generations, have been seen helpful and curative with self-experience, and do not directly conflict with both content and basic principles of modern medical scholarship. For this reason, the concept of traditional medicine does not embrace wholly all folk medicine knowledge which is more extensive and contentful. The beneficial and experienced practices in folk medicine have been performed in our country as well as the world by two schools: Healers and physicians. The license to practice in the area of TM has been given to physicians and dentists by the code that issued in 2014 by Republic of Turkey Ministry of Health. After this regulation, a discussion and competition has started in the area of practice between schools. In this study approaches of the practitioners from both parties and the view of their patients related to healing process have been compilated. How the cupping therapy is practiced by self-trained healers and medical scholars as a healing method and how much this very practice coincided with the original form of folk are questioned as well. The question of whether the cupping therapy as originally formed among folk is really beneficial, and folk’s experiential knowledge has been verified by experiments have also been looked closer.